(untitled) (ENTHYMEMA, 2022)
Drawing on Michel de Certeau’s seminal study The Practice of Everyday Life, the author argues that Dmitrii Danilov’s travel writing (Twenty Cities, 2007-2009) reimagines Russia’s symbolic geography by destabilizing the traditional opposition centre – periphery. Rather than depicting the provincial world as either an absurd and horrid world, or as a repository of ‘true Russianness’, Danilov provides a ‘decentred’ perspective on the provinces that asserts the uniqueness of each city he visits. The novel Description of a City (2012), however, resurrects the more traditional view of the provinces as a world of boredom and cultural lack. To analyse this development the article looks at the central figure of the sluggish traveller-narrator, the employment of ‘camera-eye narration’ and other, mainly linguistic, devices that reaffirm the notion of the provincial city’s ‘namelessness’ as one of its most defining characteristics.